It takes two flints to make a fire: Understanding work engagement at the team level - Costa, Patrícia Lopes (2015)
The main goal of the present thesis is to propose, validate and understand the construct of team work engagement. The thesis includes one theoretical article and five empirical articles. Theoretically, team work engagement is defined as a shared emergent state that mediates the relationship between interpersonal team processes and team effectiveness. In studies 1 and 2, we aimed at validating the construct. Our results indicate that work engagement can be empirically assessed at the individual and team levels. Moreover, the findings support the proposed mediation role of team work engagement. Study 3 was aimed at investigating a specific interpersonal team process variable, team conflict, in the relationship between team resources and team effectiveness. Results show that task and relationship conflict are contextual variables that have a negative impact on team work engagement. Task conflict, however, can strengthen the positive relationship between team work engagement and team performance. In study 4 we investigated the cross-level influence of team work engagement and individual positive emotions on perceptions of team viability. Our results indicate that team-level states have a “protective” effect on this specific outcome. Finally, study 5 takes a qualitative look at team members’ interactions, looking for patterns that characterize highly engaged teams. We found that positive affective interactions are frequent within these teams, but that the relationship between affective interactions and team objective performance is not linear. This work contributes to our understanding of teamwork, particularly its affective properties. The thesis also feeds the discussion of multilevel phenomena in organizational life, highlighting relevant clues for managing teams.